Peer Mentoring dalam Pendidikan Pesantren: Peran Mujannib dalam Pembinaan Ibadah dan Disiplin Belajar Santri - Muhammad Farij Al-Kahfi; M. Affan Ramadhan; Sibawaihi Sibawaihi (IIQ An Nur Yogyakarta, 2026)
This study aims to gain an in-depth understanding of the role of mujannib in fostering religious practices and learning discipline among students (santri) at Pesantren As-Sakinah Yogyakarta. The research problem focuses on how the mujannib system, as a peer-mentoring mechanism, contributes to shaping students’ religious character and discipline within the pesantren environment. Conceptually, this study occupies a significant position in Islamic education research because it reveals the dynamics of character formation based on role modeling and peer tutoring area that remains understudied, particularly in modern pesantren. This study employs a qualitative approach with data collected through observations, interviews, and documentation involving three groups of informants: mujannib, junior santri, and musyrif. The data were analyzed using the Miles and Huberman model, which includes data collection, data display, and conclusion drawing. The findings indicate that mujannib play a crucial role as role models and as intermediaries between musyrif and junior santri in religious activities and study discipline. The implementation of the mujannib role is reflected in activities such as leading nightly prayers, guiding congregational prayer, and supervising evening study sessions. Supporting factors include strong support from musyrif, solidarity among mujannib, and the pesantren’s religious environment. Meanwhile, the obstacles encountered involve limited time, differences in students’ personalities, and the dual dilemma of being both a peer and a mentor.